The promotion of sleep wellness: Resilience as a protective factor - Allan, Alexa C.; Gamaldo, Alyssa A.; Gamaldo, Charlene E.; Gunia, Brian C.; Al Abdul Razzak, Iyiad Mohamed; Ighodaro, Edoghogho; Salas, Rachel Marie E. (Frontiers in Sleep, 2023)
Objectives To evaluate the association between resilience, sleep quality, and health. Methods This cross-sectional study included 190 patients (Mean age = 51, SD = 15.57) recruited from the Johns Hopkins Center for Sleep and Wellness. Patients completed a modified version of the brief resilience scale (BRS) to assess characteristics of resilience and questions to assess aspects of mental health, physical health, sleep quality, and daytime functioning. Results Participants’ average score on the BRS was 4.67 (SD = 1.32, range = 1.17 – 7), reflecting a high level of resilience. There was a significant gender difference in resilience levels for men (Mean = 5.04, SD = 1.14) and women (Mean = 4.30, SD = 1.38), such that men reported significantly higher levels of resilience compared to women (t(188) = 4.02, p < .001). Lower levels of resilience were significantly associated with higher levels of (current) fatigue and tiredness after adjusting for demographic, physical, and mental covariates. In those reporting between one and three mental health symptoms, high levels of resilience minimized the negative influence that these symptoms had on sleep quality. This minimizing effect was no longer evident in those experiencing >3 mental health symptoms, who also reported significantly higher symptoms of fatigue despite their high resilience scores. Conclusions This study emphasizes how resilience may affect the relationship between mental health and sleep quality in sleep patients. Resilience may further our understanding of the inter-relationships between sleep and the manifestation of physical health symptoms, a relationship that will likely heighten in relevance during personal and global crisis. An awareness of this interaction could be used as a proactive prevention and treatment strategy. In other words, incorporating methods to evaluate resilience in patients with mental illnesses regularly can be useful for predicting the potential manifestation and severity of sleep disturbance. Therefore, strategies that focus on promoting resilience could improve health and wellness.